Simulation of the ion cyclotron range of frequencies slow wave and the lower hybrid resonance in 3D in RAPLICASOL. (10th October 2019) - Usoltceva, M; Ochoukov, R; Tierens, W; Kostic, A; Crombé, K; Heuraux, S; Noterdaeme, J-M
Abstract: Ion cyclotron range of frequencies (ICRF) wave propagation is calculated theoretically for tokamak conditions and for linear magnetized plasma device IShTAR which is dedicated to the RF sheath studies. Only the slow wave (SW) mode of ICRF waves can propagate and be studied in IShTAR. Therefore it is possible to decouple the role of the different ICRF modes in the RF sheath effects. Numerical simulations of the ICRF SW are done in COMSOL in the framework of the existing cold plasma modelling package RAPLICASOL and the SW is for the first time modelled in 3D. To date, RAPLICASOL existed as a 3D wave coupling modelling approach which targets the fast wave (FW). Plasma is implemented as a material with manually assigned physical properties and a perfectly matched layer (PML) is used to absorb the wave energy. Here it is demonstarted how to adjust the RAPLICASOL PML for models with propagating SW. Field structures in the resonance cone shape obtained for the SW differ significantly from the FW and exhibit strong dependence on the density profile in the close proximity of the antenna. The lower-hybrid (LH) resonance is a constant issue in the attempts to model the SW. In this work an approach to obtain correct numerical solutions in the LH resonance presence is demonstrated. Results of this work can be used to improve the complex tokamak ICRF simulations, where so far the SW propagation on the edge has been avoided.